Maria Mina, Sevi Triantaphyllou and Yannis Papadatos (eds). An archaeology of prehistoric bodies and embodied identities in the Eastern Mediterranean. - Gallou, Chrysanthi (Journal of Greek Archaeology, 2018)
This edited volume publishes the proceedings of the international conference Embodied Identities in the Prehistoric Mediterranean: Convergence of Theory and Practice, held in Nicosia, Cyprus, on 10–12 April 2012. The twenty–nine contributions published here ‘connect archaeologists working in the eastern Mediterranean beyond the regional limits of their area of expertise, to the broader debates currently contested in the archaeology of the body’ (p. v.). This well–produced volume is efficiently organised around six broad themes: the represented body; material culture and the construction of identities; ritualised practice and the performance of identities; embodied knowledge through technology and space; the lived body and identities; interaction with the dead body.